Grounding claims for environmental justice in the face of natural heterogeneities - Ott, Konrad (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The article wishes to analyze the ethical foundations of claims for environmental justice. By doing so, it addresses the contested relation between equality and justice. The article also wishes to shed some light into the deep religious background of egalitarian justice. Two sections deal with basic distinctions in theories of justice, as the ‘equality of what?’-debate and the problem of intrinsic value of equality. Three normative pillars of environmental justice are proposed: a) legal and political equality, b) sufficiency-thresholds, and c) obligations against victimization. These pillars are to be applied to environmental geographical topics, facing the problem of natural heterogeneities, unequal environmental endowments and economic structures. The article intends to provide the reader with conceptual ethical devices and, by doing so, to enable her making solid claims for environmental justice.